2011
DOI: 10.1080/19415257.2010.527761
|View full text |Cite
|
Sign up to set email alerts
|

A Vygotskian theory‐based professional development: implications for culturally diverse classrooms

Abstract: Professional development is defined as the main route to quality teaching, which in turn leads to improved learning for all students. Because the real challenges of professional development become apparent only after the implementation process has begun, the present paper focuses on integrating professional development experiences with classroom practices. The challenges of implementation increase as the student population becomes more diversified due to demographic changes. With Vygotsky's views of developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The impact of PD on student learning was rarely evaluated by schools, and if done so, was rarely executed very effectively (Porritt 2009a, Ofsted 2010. Eun (2011) cites Frechtling et al (1995 in identifying that the literature does not offer much on the impact of PD at the classroom level. Despite the existence of a range of models for evaluating impact, it is often not clear which model or approach, if any, is being used in school situations.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of PD on student learning was rarely evaluated by schools, and if done so, was rarely executed very effectively (Porritt 2009a, Ofsted 2010. Eun (2011) cites Frechtling et al (1995 in identifying that the literature does not offer much on the impact of PD at the classroom level. Despite the existence of a range of models for evaluating impact, it is often not clear which model or approach, if any, is being used in school situations.…”
Section: Introductionmentioning
confidence: 99%
“…It is hoped that this research goes some way to addressing this, and builds on work that has previously been done in this field (Sleeter 2001, Au and Blake 2003, Marx 2011. Other research in culturally diverse classrooms has also shown that culture is dynamic and changing, and that the cultural resources represented by the pupils can actually help teachers to develop new understandings and build classroom practice (Eun 2011). Findings from other studies also support this, and show that teachers who differ in terms of cultural identity from their pupils often benefit from being in a diverse community (Au and Blake 2003).…”
Section: Contextmentioning
confidence: 78%
“…She noted how 'the reading really encourages me and backs up my practice'. Her engagement in this process enabled a sense of permission, empowerment and justification of participatory teaching in terms of her own professional development as well as her teaching (Eun, 2011). It was their desire for relevant reading that essentially provided the courage, which allowed / enabled them to leave the shores of certainty and overcome their fears (presencing) (Hassan, 2005).…”
Section: We All Make Assumptions About How We Think We Know Best and mentioning
confidence: 99%